Characterization and prevalence of Solobacterium moorei associated with oral halitosis - Haraszthy, V I; Gerber, D; Clark, B; Moses, P; Parker, C; Sreenivasan, P K; Zambon, J J (Journal of breath research, 2008)
Previous studies suggest that Solobacterium moorei is associated with oral halitosis. In the present study, we examined the prevalence of S. moorei on the dorsal surface of the tongue in 57 adults (21 with and 36 without halitosis) by bacterial culture and direct amplification of nucleic acids. We also examined the S. moorei type strain and four clinical isolates for 16S ribosomal nucleic acid sequence, H(2)S and enzyme production, and antibiotic susceptibility. S. moorei was found on the dorsal surface of the tongue in 100% of the subjects with halitosis and 14% of subjects without halitosis. Infection with S. moorei was correlated with organoleptic measures of halitosis and with volatile sulfur compound levels. Nucleic acid probe detection of S. moorei as a test for halitosis exhibited 100% sensitivity and 86% specificity. The S. moorei type strain and all four clinical isolates showed >98% 16S rDNA sequence similarity, produced H(2)S, demonstrated acid phosphatase, beta-galactosidase, alpha-glucosidase, esterase, leucine arylamidase and naphthol phosphohydrolase enzyme activities, and were sensitive to all antibiotics tested except gentamicin, kanamycin, nalidixic acid and rifampin. This study supports the hypothesis that S. moorei is associated with halitosis.